(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. La confessione dei Testimoni di Geova e il nodo dei principi religiosi tra politica e diritto - 3. Il nodo dell’intesa. Le tappe del negoziato - 4. L’impasse e le difficili vie d’uscita. On the State-Christian Congregation of Jehovah’s Witnesses agreement ABSTRACT: To date, the State-Christian Congregation of Jehovah’s Witnesses agreement is waiting to complete the procedure within the meaning of article 8, paragraph 3, of the Italian Constitution. The latest statements by the government refer to the need for further information on health matters, evoking the issue of refusal of blood transfusion treatments. On a legal level, there are difficulties in overcoming the impasse in which the agreement is, also because there isn’t a legislative discipline of the procedure prefigured in the article 8 of the Constitution; furthermore the statements made in 2016 by the Constitutional Court on the political nature of the government’s choices regarding the agreements can be an obstacle. The paper deals with these points, also taking into account the application to the ECHR presented by the Christian Congregation of Jehovah’s Witnesses against the Italian Republic.